Designing and evaluating analytical parameters to adapt siemens urinary creatinine enzymatic method to open system analysers - Ashraf Mina; Leah McNeice; Shanmugam Banukumar; Santiago Vazquez (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2020)
Urinary creatinine is measured to assess kidney function and also as part of sample validity testing in drugs of abuse. Creatinine methods based on alkaline picrate Jaffé's reaction require extra cleaning on chemistry analysers to minimise any interference from picric acid and sodium hydroxide on other reagents on board. Enzymatic methods reagents are not as invasive and more specific. Siemens enzymatic method is more sensitive and specific when compared to Thermo Fisher alkaline picrate method but there were no available analytical parameters to setup the Siemens enzymatic method on Beckman-Coulter AU5800 analyser as an open system analyser. Emulating setup parameters from Siemens chemistry analysers did not work. The analytical parameters were developed through systematic testing using different settings to adopt and optimise the method. A full correlation was performed using the developed parameters with alkaline picrate method. The Deming regression weighted analysis for 438 samples showed a good correlation at a 95% confidence interval. Slope is 1.029 to 1.041, Y-intercept when X=0.0 is -0.9156 to -0.7481 and correlation coefficient (r) is 0.998. Alkaline picrate method Mean and SD is 12.059 and 7.248 respectively and for the Enzymatic method is 11.653 and 7.504 respectively. Many interferences from drugs and other substances are eliminated when using the enzymatic method and the stability of other reagents on-board improved because the reagents used in the enzymatic method are less invasive.